Comparative Study on the Indoor Air Quality in Critical Areas of Hospitals in Malaysia - Teck Seng, Kerk; Chia Shen, Lee; Sin Ling, Ngo; Pei Chin, Sim; Jia Xin, Tan; Kai En, Tan; Ahmed Jama, Adnaan; Hariri, Azian; Nasir, Nurul Fitriah (2023)
Indoor Air Quality (IAQ) is the air quality within and around buildings and structures, particularly regarding building occupants’ health and comfort. IAQ assessments were performed using an objective measurement of molecular gaseous pollutants to determine the IAQ profile in the hospital’s critical areas. It also analyses the effects on patients in different environments and the sources that result in deviations from approved criteria. This comparative study is aimed to investigate the concentration of different compounds in different critical departments in the hospital and propose solutions to the related problem as an improvement in indoor air quality. The data was compared with the standards and regulations. It was found that the TVOC level in the CCU department, specifically in the fluoroscopy room, has exceeded the allowable limit. A few suggestions have been raised to lower the exceeded value. The risks and symptoms held by the occupants in the hospital buildings if they face poor indoor air quality were discussed. Further study can be conducted to relate the short and long-term health issues among medical staff to poor indoor air quality